TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN ASI EKSLUSIF DI PUSKESMAS WATES KABUPATEN KULON PROGO YOGYAKARTA - Adhisty, Yulia (Akademi Kebidanan Mulia Madani Yogyakarta, 2024)
Background: Efforts to improve the quality of human resources are by giving exclusive breastfeeding to new babies during the first six months of their life, without providing additional food except drugs and vitamins. Babies are not given additional fluids or complementary foods (Zuhroh, 2022). Objective: To find out the level of knowledge of mothers about exclusive breastfeeding at the Wates Health Center, Kulon Progo Regency based on knowledge, age, education, experience, and occupation. Research Method: This type of study uses a Cross Sectional quantitative approach, the population of all mothers who have babies aged 0-6 months at the Wates Health Center, Kulon Progo Regency during April 2024-May 2024 with a total of 136 maternal respondents. The sample method was an accidental sampling method of 32 respondents. The analysis uses Unvariate Analysis with a percentage formula. Results: The results of the research from 32 respondents (100%) showed that most of them were well knowledgeable, as many as 30 respondents (93.75%), and 2 respondents (6.25%) were sufficiently knowledgeable. The majority of mothers aged 20-35 years were 24 respondents (75%), most of the mothers had high school/equivalent education as many as 23 respondents (71.9%) and 8 respondents (25%). The majority of mothers experienced giving birth to multiple para as many as 17 respondents (53.1%) and the majority of working mothers as many as 18 respondents (56.2%). Conclusion: The level of knowledge of mothers about exclusive breastfeeding at the Wates Health Center, Kulon Progo Regency, the majority of them were well knowledged, as many as 30 respondents (93.75%), enough as many as 2 respondents (6.25%). The majority of mothers aged 20-35 years were 24 respondents (75%), 23 respondents (71.9%) had high school education, and 17 respondents (53.1%) had experience in giving birth to multiple women. The majority of working mothers were 18 respondents (56.2%).